2021
DOI: 10.1038/s41525-021-00241-5
|View full text |Cite|
|
Sign up to set email alerts
|

Application of full-genome analysis to diagnose rare monogenic disorders

Abstract: Current genetic testenhancer and narrows the diagnostic intervals for rare diseases provide a diagnosis in only a modest proportion of cases. The Full-Genome Analysis method, FGA, combines long-range assembly and whole-genome sequencing to detect small variants, structural variants with breakpoint resolution, and phasing. We built a variant prioritization pipeline and tested FGA’s utility for diagnosis of rare diseases in a clinical setting. FGA identified structural variants and small variants with an overall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…In a single assay, OGM can accurately identify both balanced and unbalanced SVs, triploidy, and large AOHs, thereby mitigating the need of additional testing. Taken together, these results and other studies showing high concordance of OGM with standard of care 27 and increased ability to detect pathogenic findings 28 . This study is in agreement with published findings from multiple investigators recommending the implementation of OGM as a first-tier testing method that provides comprehensive results in a cost effective and streamlined workflow.…”
Section: Discussionsupporting
confidence: 85%
“…In a single assay, OGM can accurately identify both balanced and unbalanced SVs, triploidy, and large AOHs, thereby mitigating the need of additional testing. Taken together, these results and other studies showing high concordance of OGM with standard of care 27 and increased ability to detect pathogenic findings 28 . This study is in agreement with published findings from multiple investigators recommending the implementation of OGM as a first-tier testing method that provides comprehensive results in a cost effective and streamlined workflow.…”
Section: Discussionsupporting
confidence: 85%
“…MPseq is a powerful technique for detection of genomic fusions in a whole genome approach and obviates some of the ambiguity of short read sequencing [39]. Our study was not directed at a comparison of OGM with any of the NGS-based approaches, but other studies have shown that OGM and WGS identify different, albeit overlapping, sets of SVs, suggesting potential synergy of the two methods [38,[40][41][42]. However, all NGS based approaches share several major hurdles, including equipment price, complexity of the sequence library preparation, and data analysis intricacy.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of this for genetic disease diagnosis is not yet known. Further studies are needed to compare the diagnostic performance of these methods versus hybrid methods with short read sequencing and complementary technologies, such as long-read sequencing and optical mapping 74 , 77 , 78 .…”
Section: Discussionmentioning
confidence: 99%